Exosomal miR-17-3p Alleviates Programmed Necrosis in Cardiac Ischemia/Reperfusion Injury by Regulating TIMP3 Expression. (25th January 2022) - Liu, Zhuyuan; Zhu, Didi; Yu, Fuchao; Yang, Mingming; Huang, Dan; Ji, Zhenjun; Lu, Wenbin; Ma, Genshan
Abstract : Objective . Myocardial ischemia/reperfusion (I/R) injury can aggravate myocardial injury. Programmed necrosis plays a crucial role in this injury. However, the role of exosomal miRNAs in myocardial I/R injury remains unclear. Therefore, this study is aimed at exploring the function and mechanism of exosomal miR-17-3p in myocardial I/R injury. Methods . The myocardial I/R injury animal model was established in C57BL/6 mice. Exosomes were identified using transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA), and Western blotting. Programmed necrosis was detected by PI staining. Heart function and myocardial infarct size were evaluated using echocardiography and triphenyl tetrazolium chloride (TTC) staining, respectively. Histopathological changes were visualized by hematoxylin and eosin (H&E) and Masson staining. The regulation of TIMP3 expression by miR-17-3p was verified using a dual-luciferase reporter assay. Lactate dehydrogenase (LDH) and tumor necrosis factor- α (TNF- α ) levels were measured by enzyme-linked immunosorbent assays (ELISA). TIMP3 expression was measured by quantitative reverse transcription-polymerase chain reaction (qRT-PCR) and Western blotting. Results . We demonstrated that miR-17-3p was significantly downregulated in peripheral blood exosomes after cardiac I/R injury. Further analysis indicated that exosomal miR-17-3p attenuated H2 O2 -induced programmed necrosis in cardiomyocytes in vitro. Moreover, TIMP3 was a target for miR-17-3p. TIMP3 affected H2 O2 -induced programmed necrosis in cardiomyocytes. This effect was modulated by miR-17-3p in vitro. Furthermore, exosomal miR-17-3p greatly alleviated cardiac I/R injury in vivo. Conclusions . The present study demonstrated that exosomal miR-17-3p alleviated the programmed necrosis associated with cardiac I/R injury by regulating TIMP3 expression. These findings could represent a potential treatment for I/R injury.